Pedagogical Transformation in the Technological Era: A Qualitative Study of Digital Education Practices in Indonesian Senior High Schools - Minarto, Agus; Muhajir, Muhajir; Hatip, Ahmad (Journal of Social Work and Science Education, 2025)
This study explores the pedagogical transformation driven by digital education technologies in Indonesian State Senior High Schools, particularly in Pamekasan Regency. Employing a qualitative approach, data were collected through in-depth interviews, classroom observations, and document analysis from 15 teachers and 20 students. Thematic analysis was used to identify core patterns and themes. Results reveal significant shifts in the teaching and learning paradigm, where digital tools such as Google Classroom and Zoom enable more flexible, accessible, and student-centered learning. However, challenges such as limited infrastructure, digital skill gaps, and reduced face-to-face interaction persist. The role of educators is evolving from knowledge transmitters to facilitators. Successful implementation of digital education requires robust infrastructure, sustained teacher training, and inclusive policies. Policymakers should prioritize equitable access to digital tools and upskilling programs for educators. Future research should expand geographically and adopt mixed methods to improve generalizability.